Umetnostna besedila pri pouku slovenščine kot drugega/tujega jezika - Pezdirc-Bartol, Mateja (Jezik in slovstvo, 1998)
Attention focuses on some basic questions facing the teacher when he/she wants to use literary texts in teaching Slovenian as a second/foreign language. Reason are given for including literry texts in these courses and factors discussed that to be taken into consideration when selecting texts and desining efficient classroom activities.
Keywords: Slovene; slovenščina; didactic method; didaktika; slovenščina kot drugi ali tuji jezik; umetnostna besedila